A Smart GSM-Based Home Electrical Appliances Remote Control System - Elvis Tamakloe; Benjamin Kommey (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2022)
Energy control systems have over the years experienced significant transformation due to technological innovations. Its importance has led to the development of a few models aimed at realizing home automation and resolving energy wastage. Wise use of electricity helps a nation to become more energy-efficient, reduces the environmental impact, saves money on the electricity bills, and keeps the nation’s electricity supply more reliable. This paper presents a prototype design to reduce the electricity wastage in Ghanaian homes and probably offices. A Global System for Mobiles (GSM) module is used for receiving short message service (SMS) from user’s mobile phone that automatically enable the controller to take any further action such as to switch ON or OFF the home electrical appliances like light, air-conditioner, fan etc. The system is activated when user sends the SMS to the microcontroller and upon receiving the SMS command, the microcontroller unit then automatically controls the home electrical appliances by switching ON or OFF the device accordingly. A system prototype was developed and tested successfully. The system provides an effective mechanism to aid the efficient utilization of power in a developing country such as Ghana